Lymphatic malformations: a 9-year experience at the vascular anomaly clinic - Amr Abdelhamid AbouZeid; Shaimaa Abdelsattar Mohammad; Nihal Hussein Aly; Wael Ahmed Ghanem; Mohammad Seada; Iman A. Ragab; Osama El-Naggar; Mohamed Aly AbdelBaky (SpringerOpen, 2023)
Abstract Purpose To share our experience in the management of a specific type of vascular malformations (lymphatic) at a specialized multidisciplinary clinic for vascular anomalies. Methods Data of patients attending the vascular anomaly clinic during the period 2015 through 2023 were retrospectively analyzed. The study included cases diagnosed primarily as lymphatic malformations (LMs). We excluded cases associated with complex/syndromic vascular malformations. Available data included regional distribution of the LMs, age at presentation, sex, imaging studies, and different modes of treatment. Results The study included 131 cases of LMs whose data were available for retrospective analysis. Generally, LMs had a benign course with good prognosis apart from two recorded mortalities (1.5%) during the 9-year period of the study. In this series, 93 cases were managed by injection sclerotherapy (Bleomycin). About 57 cases showed satisfactory response to injection sclerotherapy alone without the need to add other treatment modalities. Forty cases underwent surgical excision/debulking. Postoperative wound complications were recorded in 5 cases (12.5%). Sirolimus was offered for patients with LMs after the failure of conventional treatment (injection/surgery) to control associated significant complications. Conclusion Lymphatic malformations represent a common presentation at the vascular anomaly clinic, which usually have a benign course. Complications are mainly cosmetic especially when involving the face, and sometimes superadded infections may occur. Airway compromise is a potential serious complication with submandibular lymphatic malformations in the neck.